2019
DOI: 10.1038/s41398-019-0672-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced visual evoked potential amplitude in autism spectrum disorder, a variability effect?

Abstract: Atypical sensory behaviours represent a core symptom of autism spectrum disorder (ASD). Investigating early visual processing is crucial to deepen our understanding of higher-level processes. Visual evoked potentials (VEPs) to pattern-reversal checkerboards were recorded in ASD children and age-matched controls. Peak analysis of the P100 component and two types of single-trial analyses were carried out. P100 amplitude was reduced in the ASD group, consistent with previous reports. The analysis of the proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 56 publications
(80 reference statements)
3
29
3
Order By: Relevance
“…Atypicalities in sensory-evoked neural responses and behavioral performance have been widely reported in ASD, including altered responses to visual (2,49,58), auditory (59), and somatosensory stimuli (60)(61)(62). Moreover, in some studies, higher inter-participant (48-50) and within-participant inter-trial (51-53) variability of brain responses to sensory stimuli has been shown.…”
Section: Intraclass Correlation Coefficient (Icc) Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atypicalities in sensory-evoked neural responses and behavioral performance have been widely reported in ASD, including altered responses to visual (2,49,58), auditory (59), and somatosensory stimuli (60)(61)(62). Moreover, in some studies, higher inter-participant (48-50) and within-participant inter-trial (51-53) variability of brain responses to sensory stimuli has been shown.…”
Section: Intraclass Correlation Coefficient (Icc) Resultsmentioning
confidence: 99%
“…This is in line with higher inter-trial behavioral variability that was observed for individuals with ASD, measuring reaction times to executive function (63) and tactile judgment tasks (64), as well as rhythmic tapping tasks (65). The higher variability between trials and between individuals with ASD has, in turn, been interpreted in the context of neuronal processing being "noisy" or "unreliable" (e.g., (49,50,52,(66)(67)(68), but see (69,70) for reports of lower noise in ASD, and (25,26) for evidence of typical levels of noise in ASD). According to this view, high levels of endogenous neural noise in ASD render neural signals unreliable (53,71).…”
Section: Intraclass Correlation Coefficient (Icc) Resultsmentioning
confidence: 99%
“… Weinger et al (2014) reported lower signal-to-noise ratios and deficits in low-contrast responses at the stimulus frequency of 12.5 Hz in the ASD group compared to the TD group. Increased inter-trial variability in ASD that resulted in reduced P100 amplitude was recently described by Kovarski et al (2019) .…”
Section: Introductionmentioning
confidence: 83%
“…There are three major descriptive points from Fig 6 that are worth to be stressed: 1) The latency estimation appears to be reliable as shown in the sorted trials (Fig 6a b); 2) The correction of jitter in the specified time window (400 ms to 800 ms) still preserve the jitter features in other time windows (e.g., early ones, see Fig 6c); 3) The correction in the average waveform is also exclusively taking effect in relevant window (Fig 6d). Likewise, the latency jitter issue can occur in the early time window as well, and its functional relevance has been studied (Kovarski et al, 2019;Magnuson, Iarocci, Doesburg, & Moreno, 2019;Milne, 2011). To serve as a demonstration, we can specify the time window 200-400 ms encompassing the early component in the sample data.…”
Section: Simple Operations In Resync Toolboxmentioning
confidence: 99%